Policy Implementation of Electronic Regional Tax Receiving System in Tomohon City - Liuw, Friedel Wirabuana Yefta; Dilapanga, Abdul Rahman; Wawointana, Thelma (Technium Social Sciences Journal, 2023)
This study aimed to describe, analyze, and interpret how the Implementation of the Electronic Local Tax Revenue System Policy in the city of Tomohon. This study uses a qualitative method, with the focus of research namely the mechanism of the electronic regional tax revenue system in the city of Tomohon and what factors are the obstacles. Data collection techniques were carried out by means of observation, interviews, and document studies. The research location is the Regional Revenue and Financial Management Agency of Tomohon City as the tax collection agency. The results of the study show that the implementation of the electronic regional tax revenue system policy in Tomohon City has not run optimally. Findings in the field show that the implementation of this policy 1) has not been supported by the capability of the Human Resources of the Policy implementers; 2) has not been supported by the ability of adequate Resources for Facilities and Infrastructure; 3) both collection officers and taxpayers have not received socialization and education regarding this regional regulation; 4) Required leadership disposition in following up the implementation of this electronic regional tax revenue system policy; and 5) It is necessary to issue a derivative regulation from Regional Regulation Number 1 of 2018 in a regional head regulation. The factors that hinder the implementation of this policy are (1) the implementation structure is not structured effectively, (2) the lack of implementing capacity and capability (the required human resources are not appropriate/appropriate), (3) the lack of organizational capacity and capability of the institutions implementing institutions, (4) Weak implementation management, (5) Lack of resources (budget, tools, time). Regional governments in making a policy must understand, analyze, and pay attention to HR capabilities, provide supporting facilities and infrastructure, follow up on leadership dispositions, issue supporting regulations, and need to review Regional Regulation number 1 of 2018 in the framework of optimizing the Electronic Regional Tax Revenue System Policy In Tomah City.